SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL EVALUATION OF SOME TETRAHYDROQUINAZOLINE DERIVATIVES OF BENZO[B]THIOPHENE (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
In the present investigation, synthesis of 4-(1-(3-chlorobenzo[b]thiophene-2-carbonyl)-1H-indol-3-yl)-7, 7-dimethyl-3, 4, 7, 8-tetrahydroquinazoline2, 5(1H, 6H)dione (3a-d) is described. These unreported compounds are obtained starting from indole- 3-aldehyde and3-chloro-1benzothiophene-2-carbonylchloride (1a-d). A series of compounds (3a-d) were prepared. The structures of the newly synthesized compounds were elucidated on the basis of IR and 1H NMR spectral data of the compounds. All the compounds have been screened for antibacterial activity against S. aureus, E. coli, and P. aeruginosa and for antifungal activity against Candida albicans, A. niger, and A. clavatus using broth dilution method and they were found to exhibit good to moderate antimicrobial activity.